2007
DOI: 10.1007/s11694-007-9012-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on the measurement of NaCl content of aqueous solution by short-wavelength near infrared spectroscopy (SW-NIR)

Abstract: Short-wavelength near infrared (SW-NIR) spectroscopy can provide a rapid and nondestructive determination of salt content in food products, and potentially monitor salt concentration of brines during processing. This is of significant importance for ensuring the safety and quality of cured and smoked foods. One of the constraints is having reliable models to predict salt concentration as temperature varies. The effect of temperature (4.0-42.9°C) on SW-NIR spectra (594-1,105 nm) of aqueous salt solution (0-10.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…As shown in Figure 6 , half the number of filters (#1, #2, #5, #6, #7, #14, #15, and #16) have high activations on variables between 960~980 nm, and the theoretical peak around 970 nm is related to the third overtones of O-H bonds in water [ 19 ]. Seven filters (#1, #2, #6, #7, #10, #15, #16) have high responses on variables between 840~860 nm, which around the O-H weak absorption bands [ 20 ]. The uninformative variables are reduced to zero.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 6 , half the number of filters (#1, #2, #5, #6, #7, #14, #15, and #16) have high activations on variables between 960~980 nm, and the theoretical peak around 970 nm is related to the third overtones of O-H bonds in water [ 19 ]. Seven filters (#1, #2, #6, #7, #10, #15, #16) have high responses on variables between 840~860 nm, which around the O-H weak absorption bands [ 20 ]. The uninformative variables are reduced to zero.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1 , the key chemical features appear near the ~970 nm, which is related to the third overtones of O-H bonds in water [ 19 ]. The small mounds near ~840 nm and ~750 nm, which can be correlated to 2 v 1 + v 2 + v 3 and 3 v 1 + v 3 combination transition, respectively, where v 1 is the symmetric O-H stretch, v 2 is the O-H bending mode, and v 3 is the antisymmetric O-H stretch [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many investigations have reported the influence of temperature on spectral measurements of food systems, chemical materials, and some complex mixtures [6][7][8][9]. These investigations indicated that spectral measurements of the samples are affected by temperature.…”
Section: Introductionmentioning
confidence: 99%